Texture analysis for estimating spatial variability and anisotropy in planar stochastic structures - Scharcanski, Jacob; Dodson, C. T. J (Optical Engineering, 1996)
Some operators from the theory of texture image analysis are used to obtain a new method for the evaluation of anisotropy in planar stochastic structures. A local gradient function provides information on local anisotropy and its variability, from 2-D density images for foil materials like polymer sheets, nonwoven textiles and paper. Such images can be captured by radiography or light transmission; results are reported for a range of paper structures. The method has potential for on-line application to monitoring and control of anisotropy and its variability, as well as local density itself, in continuous manufacturing processes. ©